STUDI LITERATUR: MENGKAJI KONTRIBUSI KONSELING KELOMPOK TERHADAP MENINGKATKAN KECERDASAN EMOSIONAL SISWA - Pratama, Muhammad Bagas Putra; Amelinda, Yesi; Ningsih, Nova Tri Wulan Wahyu; Prameswari, Ajeng Chandra; Dewi, Ratna Sari; Minarsi, Minarsi (Universitas Muria Kudus, 2025)
Emotional intelligence plays an important role in individual development, especially for students who face various challenges in social and academic environments. The ability to recognize, control, and express emotions well greatly affects their mental health and social relationships. One effective strategy in improving students' emotional intelligence and self-control is group counseling. This study aims to explore the effectiveness of various group counseling techniques in improving students' emotional intelligence and self-control. Using a qualitative method with a literature study approach, this research analyzed various techniques such as REBT, Symbolic Modeling, Role Playing, WDEP, Ability Potential Response (APR), Psychodrama, and Sociodrama. The results showed that group counseling made a significant contribution in helping students recognize, manage, and express emotions better. Direct experience-based techniques and cognitive reflection proved to be more effective than conventional methods. Therefore, counselors are advised to apply techniques that suit students' needs to support their emotional and social development.